2020
DOI: 10.1038/s41594-020-0445-1
|View full text |Cite
|
Sign up to set email alerts
|

Dppa2 and Dppa4 counteract de novo methylation to establish a permissive epigenome for development

Abstract: Early mammalian development entails genome-wide epigenome remodeling, including DNA methylation erasure and reacquisition, which facilitates developmental competence. To uncover the mechanisms that orchestrate DNA methylation (DNAme) dynamics, we coupled a single-cell ratiometric DNAme reporter with unbiased CRISPR screening in ESC. We identify key genes and regulatory pathways that drive global DNA hypomethylation, and characterise roles for Cop1 and Dusp6. We also identify Dppa2 and Dppa4 as essential safegu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 68 publications
11
59
0
Order By: Relevance
“…Loss of bivalent H3K4me3 through knocking out MLL2/KMT2B is associated with impaired activation of developmental genes and subsequent embryonic lethality ( Glaser et al., 2009 ; Xiang et al., 2019 ). More recently, DPPA2 and DPPA4 have been shown to function as epigenetic priming factors to facilitate bivalency establishment and counteract with DNA methylation in developmental genes ( Eckersley-Maslin et al., 2020 ; Gretarsson and Hackett, 2020 ).
Figure 4 Establishment of the Embryonic Epigenome during Mammalian Early Development A schematic model showing sequential establishment of embryonic epigenome in mammalian early development.
…”
Section: Main Textmentioning
confidence: 99%
“…Loss of bivalent H3K4me3 through knocking out MLL2/KMT2B is associated with impaired activation of developmental genes and subsequent embryonic lethality ( Glaser et al., 2009 ; Xiang et al., 2019 ). More recently, DPPA2 and DPPA4 have been shown to function as epigenetic priming factors to facilitate bivalency establishment and counteract with DNA methylation in developmental genes ( Eckersley-Maslin et al., 2020 ; Gretarsson and Hackett, 2020 ).
Figure 4 Establishment of the Embryonic Epigenome during Mammalian Early Development A schematic model showing sequential establishment of embryonic epigenome in mammalian early development.
…”
Section: Main Textmentioning
confidence: 99%
“…Studies have shown that both H3K9me3 and H3K27me3 act as epigenetic barriers for SCNT reprogramming, and overexpression of their de-methylases Kdm4b and Kdm4d could improve reprogramming efficiency ( Liu W. et al, 2016 ; Matoba et al, 2018 ). Thereby, it is possible that experimental ways to induce de-methylation of candidate barrier genes (such as Dapp2, Dapp4, Obox6, Tead4) or directly compensating their expression in SCNT embryo could improve efficiency of genomic reprogramming and overcome early embryonic arrest in SCNT embryos ( Eckersley-Maslin et al, 2020 ; Gretarsson and Hackett, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] However, many other chromatin modifications, such as O-GlcNAc, 5hmC or H3K4me3, are also enriched on subsets of TE, suggesting that the epigenetic regulation of mobile elements may be more complex than previously anticipated and warrants further investigation. [37][38][39][40] Notably, a significant proportion of mammalian noncoding sites enriched for chromatin modifications do not coincide with either enhancers or TE. Epigenetic aberrations at these unannotated regions have already been linked to human syndromes, [41] implying that the functional interrogation of chromatin marks at non-genic regions will be instrumental to understand the mechanisms that govern genome regulation in both physiological and pathological circumstances.…”
Section: What Is the Function Of Epigenetic Marks At Non-coding Loci?mentioning
confidence: 99%